Phage-mediated biocontrol of Pseudomonas putida and Pseudomonas fluorescens in dairy products using gelatin-based delivery - Malavika Binitha Hari; Nimisha Mahesh; S. Neeraja; Nikhil Harikumar; Ambily Vasudevan; Pradeesh Babu; Bipin G. Nair; Geetha B. Kumar; Jayalekshmi Haripriyan (International Dairy Journal, 2026)

Novel bacteriophages effectively target multidrug-resistant clinical isolates of Klebsiella pneumoniae - Malavika Binitha Hari; A. L. Sreelekshmi; Pradeesh Babu; Abhijith Pulimoottil Jaykumar; Sivaraj Barath; Sharayu Magar; Sutharsan Govindarajan; John Bernet Johnson; Anil Kumar; Jayalekshmi Haripriyan; Victor Nizet; Jason Gill; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

RECK and TIMP-2 mediate inhibition of MMP-2 and MMP-9 by Annona muricata - G Drishya; Jyotsna Nambiar; Sanu K Shaji; Muralidharan Vanuopadath; A Achuthan; Abishek Kumar; Ashna Alias; Ayesha Sherif; Catherine Joseph; P Divya; Damu Sunil Kumar; Chinchu Bose; et al. (Journal of Biosciences, 2020)

(I-3,II-3)-Biacacetin-mediated cell death involves mitochondria - Jyotsna Nambiar; Gayathri Vijayakumar; G. Drishya; Sanu K. Shaji; Nanjan Pandurangan; Geetha B. Kumar; Bipin G. Nair (Molecular and Cellular Biochemistry, 2019)

Climate change projections for Tamil Nadu, India: deriving high-resolution climate data by a downscaling approach using PRECIS - Prasanta Kumar Bal; A. Ramachandran; R. Geetha; B. Bhaskaran; P. Thirumurugan; J. Indumathi; N. Jayanthi (Theoretical and Applied Climatology, 2016)

Detection of OvHV-2 from an outbreak of sheep associated malignant catarrhal fever from crossbred cattle of Southern India - N. Vinod Kumar; B. Sreedevi; A. Karthik; S. Vijaya Lakshmi; A. Geetha Reddy; D. Sreenivasulu (Veterinary Research Communications, 2014)

Temporal Trends of Malondialdehyde in Stored Human Plasma - Arun Kumar; B. S. Dhillon; D. N. Rao; Geetha Menon; Hari Shankar; L. K. Dhaliwal; Maiti Leema; Nomita Chandhiok; Neeta Kumar; Rohini Sehgal; Suneeta Mittal; Sumitu Sahdev; et al. (Indian Journal of Clinical Biochemistry, 2012)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)